2020
DOI: 10.7860/jcdr/2020/44407.13969
|View full text |Cite
|
Sign up to set email alerts
|

Transmigrated Mandibular Canine Guided into its Normal Position

Abstract: Transmigrated mandibular canines increase treatment complexity in terms of both anchorage and biomechanical planning, posing challenges for both Orthodontists and Oral Surgeons. This case report presents the orthodontic treatment in a 12-year-old girl patient, with transmigrated and impacted mandibular right canine positioned horizontally below the apices of the mandibular incisors. The mandibular deciduous right canine was extracted followed by the traction of the transmigrated permanent canine. Eruption was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…The treatment of IMCs requires a multidisciplinary approach [27]. Just as spontaneous eruption occurs harmoniously and leads to tooth alignment in the presence of healthy periodontal tissues, the combined surgical-orthodontic treatment of an included element should simulate physiological eruption [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of IMCs requires a multidisciplinary approach [27]. Just as spontaneous eruption occurs harmoniously and leads to tooth alignment in the presence of healthy periodontal tissues, the combined surgical-orthodontic treatment of an included element should simulate physiological eruption [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the cases selected in this review, one case with gingival recession was found [28]. In all cases there was periodontal success of the treated IMCs [19][20][21][22][23][24][25][26][27]39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En caso clínico realizado en un adolescente de 12 años que se sometió a una tracción del canino izquierdo para una erupción guiada se obtuvo como resultado una oclusión funcional, mejoró la estética y se mantuvo estable luego de 1,5 años de seguimiento 23 . Su presencia resulta importante en la eficacia masticatoria, dado que da estabilidad a la arcada dentaria, mantiene la estética y una expresión facial armoniosa.…”
Section: Discussionunclassified